2005
DOI: 10.1038/sj.ijo.0803011
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular stress responsivity, body mass and abdominal adiposity

Abstract: OBJECTIVE: To assess the relationship between adiposity and cardiovascular stress reactivity and recovery in middle-aged men and women, and investigate the influence of impaired poststress cardiovascular recovery on changes in body mass index (BMI) and waist-hip ratio over 3 y. PARTICIPANTS: In total, 225 healthy men and women aged 47-59 y were recruited from the British civil service. METHODS: Laboratory mental stress testing was carried out, with blood pressure (BP), cardiac output and total peripheral resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
6
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 40 publications
4
83
6
4
Order By: Relevance
“…46 Consistent with previous results, we found a positive association between impaired post-stress recovery of diastolic BP and adiposity. 15 There was also a positive relationship at all time points between leptin levels and heart rate, independent of baseline heart rate and BMI. Chronic leptin infusion has been shown to stimulate sympathetic outflow to thermogenic and non-thermogenic organs of rodents, and to increase heart rate and arterial BP in animals.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…46 Consistent with previous results, we found a positive association between impaired post-stress recovery of diastolic BP and adiposity. 15 There was also a positive relationship at all time points between leptin levels and heart rate, independent of baseline heart rate and BMI. Chronic leptin infusion has been shown to stimulate sympathetic outflow to thermogenic and non-thermogenic organs of rodents, and to increase heart rate and arterial BP in animals.…”
Section: Discussionmentioning
confidence: 81%
“…Supporting this, a more recent analysis of middle-aged people from the Whitehall II cohort found that impaired cardiovascular recovery following an acute laboratory stressor, manifest as prolonged elevations in systolic BP and cardiac index, was longitudinally associated with central adiposity in men, predicting a 3-year increase in waist-hip ratio. 15 Several factors may contribute to individual variation in responsiveness to stress including genetic predisposition, gender, early life and current events. 5 Notably, chronic stress exposure has been associated with a dysregulated HPA and/ or SNS response, and there is growing evidence for an association between chronic stress and abdominal adiposity.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed poststress BP and heart rate variability recovery is more common in adults with a lower SES (31), and it has been associated with social isolation, poor mental health, and impaired hemostatic responses to stress (32). It also predicts future increases in BP and abdominal adiposity (33,34). Sustained reductions in heart rate variability following stress may have adverse effects on cardiovascular disease risk (35).…”
Section: Discussionmentioning
confidence: 99%
“…Reactivity and recovery regression models were adjusted for baseline levels of the relevant measure. Covariates also included age and BMI which are established predictors of basal blood pressure and cardiovascular stress reactivity (Matthews and Stoney, 1988;Steptoe and Wardle, 2005a). To control for negative affect, the negative affective items from the POMS were subsequently added as a covariate to each model.…”
Section: Discussionmentioning
confidence: 99%